PD-1 expression in transbronchial biopsies of lung transplant recipients is a possible early predictor of rejection - Righi, Ilaria; Vaira, Valentina; Morlacchi, Letizia Corinna; Croci, Giorgio Alberto; Rossetti, Valeria; Blasi, Francesco; Ferrero, Stefano; Nosotti, Mario; Rosso, Lorenzo; Clerici, Mario (Frontiers in Immunology, 2023)
Chronic lung allograft dysfunction (CLAD) is the main cause of the reduced survival of lung transplanted (LTx) patients. The possible role of immune checkpoint molecules in establishing tolerance has been scarcely investigated in the setting of lung transplantation. We conducted a retrospective, observational pilot study on a consecutive series of transbronchial cryobiopsies (TCB) obtained from 24 patients during LTx follow-up focusing on PD-1, one of the most investigated immune checkpoint molecules. Results showed that PD-1-expressing T lymphocytes were present in all TCB with a histological diagnosis of acute rejection (AR; 9/9), but not in most (11/15) of the TCB not resulting in a diagnosis of AR (p=0.0006). Notably, the presence of PD-1-expressing T lymphocytes in TCB resulted in a 10-times higher risk of developing chronic lung allograft dysfunction (CLAD), the main cause of the reduced survival of lung transplanted patients, thus being associated with a clearly worst clinical outcome. Results of this pilot study indicate a central role of PD-1 in the development of AR and its evolution towards CLAD and suggest that the evaluation of PD-1-expressing lymphocytes in TCB could offer a prognostic advantage in monitoring the onset of AR in patients who underwent lung transplantation.